Performance Comparison of SRM, PMSM & BLDC Motor Drives via Experimentation in Laboratory for EV Application - Sunil Patil, Rakesh Saxena, Yogesh Pahariya (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This paper presents comparative study of three different motor drives using advance speed controllers via experimentation in laboratory for EV application. Advance speed control technique of Switched Reluctance Motor (SRM) drive using Digital Signal Processor (DSP-28335) controller and hardware setup for experimentation is utilized. Permanent Magnet Synchronous Motor (PMSM) drive speed control method used in this paper is Sinusoidal Pulse Width Modulation (SPWM) technology supported inverter and is implemented using DSP (2812) controller hardware setup. Also, advance speed control technique of Brushless DC (BLDC) motor drive by FPGA (Field Programmable Gate Array) controller using hardware setup is adopted. These methods are more preferred in practice. Since there is ever increasing concern on the energy utilization & environmental protection, the development of Electric Vehicle (EV), using particular motor has become a hot research topic. As major part of EV have to offer high efficiency, high torque, easy control, wide speed operating range & maintenance free operations. In recent years, SRM, PMSM & BLDC motors become the best alternative to the conventional motors with all required features & capabilities for EV application. Experiments are conducted in laboratory on SRM, PMSM & BLDC drives by load tests with Digital Storage Oscilloscope (DSO). Test data along with waveform are recorded to calculate efficiency & torque. Comparative study of SRM, PMSM & BLDC drives with better torque & efficiency results for EV application are presented.